Metacognition and its interactions with cognition, affect, physicality and off-task thought inside the independent learning experience - Carson, Luke 1976- (New York, NY Routledge, 2021)
"What happens when teachers are removed from the equation, when we learn by ourselves or with peers? Increasingly rapid change is part of our world today and tomorrow. The need to learn and to adapt is now lifelong and ubiquitous. But are educators and educational institutions preparing today's students for this reality? Educators and institutions choose pedagogic models, design curricula and provide instruction. However, this does not mirror the learning environments that we inhabit outside of formal education, nor does it reflect all our learning time during formal education. This text provides a data-driven picture of the independent learning experience - what occurs in the minds of learners as they negotiate learning tasks without (or with less) guidance and instruction. Cognition, distraction, embodied experience, emotion, and metacognition are central to this learning. Drawing on new empirical data, this volume focuses on university-aged learners. These are the learners who have been through our formal educational systems. Do they learn well in independent settings? Have they been prepared for this? Through an explication of this experience, this volume makes a case for how we can better prepare them for the demands of current and future learning."
Includes bibliographical references and index.
Keywords: Independent study; Learning, Psychology of; Metacognition; Self-culture.